Long-Term Follow-up of Human Immunodeficiency Virus-Associated Pulmonary Hypertension: Clinical Features and Survival Outcomes of the Pan Africa Pulmonary Hypertension Cohort (PAPUCO) - Thienemann, Friedrich; Katoto, Patrick D M C; Azibani, Feriel; Kodogo, Vitaris; Mukasa, Sandra L; Sani, Mahmoud U; Karaye, Kamilu M; Mbanze, Irina; Mocumbi, Ana O; Dzudie, Anastase; Sliwa, Karen (Open forum infectious diseases, 2022)
Abstract Background Data characterizing risk factors and long-term outcome studies on human immunodeficiency virus (HIV)-associated pulmonary hypertension (PH) in Africa are lacking. Methods The Pan African Pulmonary Hypertension Cohort, a multinational registry of 254 consecutive patients diagnosed with PH (97% of African descent) from 9 centers in 4 African countries was implemented. We compared baseline characteristics and 3-year survival of an HIV-infected cohort newly diagnosed with PH (PH/HIV+) to an HIV-uninfected cohort with PH (PH/HIV−). Results One hundred thirty-four participants with PH completed follow up (47 PH/HIV+ and 87 PH/HIV−; age median, 36 versus 44 years; P = .0004). Cardiovascular risk factors and comorbidities were similar except for previous tuberculosis (62% versus 18%, P < .0001). Six-minute walk distance (6MWD) <300 meters was common in PH/HIV− (P = .0030), but PH/HIV+ had higher heart (P = .0160) and respiratory (P = .0374) rates. Thirty-six percent of PH/HIV+ and 15% of PH/HIV− presented with pulmonary arterial hypertension (PAH) (P = .0084), whereas 36% of PH/HIV+ and 72% of PH/HIV− exhibited PH due to left heart disease (PHLHD) (P = .0009). Pulmonary hypertension due to lung diseases and hypoxia (PHLD) was frequent in PH/HIV+ (36% versus 15%) but did not reach statistical significance. Human immunodeficiency virus-associated PAH tended to have a poorer survival rate compared with PHLHD/PHLD in HIV-infected patients. Conclusions The PH/HIV + patients were younger and commonly had previous tuberculosis compared to PH/HIV− patients. Despite a better 6MWD at presentation, they had more signs and symptoms of early onset heart failure and a worse survival rate. Early echocardiography assessment should be performed in HIV-infected patients with history of tuberculosis who present with signs and symptoms of heart failure or posttuberculosis lung disease. The HIV cohort within the Pan African Pulmonary Hypertension Cohort is particularly relevant given the colliding epidemics of HIV/tuberculosis in Africa. Due to immunosuppression, young people living with HIV/AIDS contract tuberculosis several times, increasing their risk of post-tuberculosis lung diseases and HIV-associated pulmonary hypertension in particular.